2016
DOI: 10.1111/jbg.12246
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameter estimates for prenatal and postnatal mortality in Nellore cattle

Abstract: The aim of this study was to estimate genetic parameters for prenatal (PRE) and postnatal (POS) mortality in Nellore cattle. A total of 13 141 (PRE) and 17 818 (POS) records from Nellore females were used. PRE and POS were recorded using binary scale scores: a score of '1' was given to calves that were born alive (PRE) and those that were alive at weaning (POS), and a score of '0' was given to calves that were not alive at or around birth (PRE), as well as to those weighed at birth but not at weaning (POS). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
(82 reference statements)
2
3
0
Order By: Relevance
“…The calf mortality rate until weaning was 13.7% (Table 1), which corroborates those described in previous studies, from 3 to 15% until weaning (Bunter et al, 2014;Magalhães Silva et al, 2017;Ring et al, 2018). The need for human assistance and the vigor absence imply problems for calf development, as they indicate increasing chances of pre-weaning mortality.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The calf mortality rate until weaning was 13.7% (Table 1), which corroborates those described in previous studies, from 3 to 15% until weaning (Bunter et al, 2014;Magalhães Silva et al, 2017;Ring et al, 2018). The need for human assistance and the vigor absence imply problems for calf development, as they indicate increasing chances of pre-weaning mortality.…”
Section: Resultssupporting
confidence: 90%
“…The mortality rate in Brazilian beef herds is about from 8 to 10% (Corrêa et al, 2001;Azevedo Júnior et al, 2017;Magalhães Silva et al, 2017). These authors reported that the highest percentage of calf mortality occurs in the first weeks of life.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mortality rate observed the present study (4%) was the same as was reported by Magalhães Silva et al, [33] and lower than the values reported by Bunter et al [2] and Nascimento et al [34] for a similar beef cattle production system (9.5% and 8%, respectively). Given the low mortality rate observed and the high proportion of calves evaluated with the highest score for vigor (96.2%), no association was found between these variables in the present study.…”
Section: Discussionsupporting
confidence: 85%